2009
DOI: 10.1080/10826080802483936
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Methadone Consumption: Client Issues and Stigma

Abstract: Supervised methadone consumption is an important part of methadone maintenance treatment (MMT) but may contribute to stigma for clients. Data from qualitative interviews with MMT clients (n = 64) conducted in 2002-2003 in Canada were analyzed using thematic analytic methods. Three themes dominated clients' accounts of supervised consumption (convenient access to services, relationships with pharmacists and dispensing staff, and attributes of the dispensing space) and were interwoven with experiences of stigmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 14 publications
1
103
0
1
Order By: Relevance
“…Berg et al, 2009;Eversman, 2010;Larance et al, 2011;Lin et al, 2010;Philbin & Zhang, 2010) and patient perspectives (e.g. Anstice et al, 2009;Conner & Rosen, 2008;Harris & McElrath, 2012;Lin et al, 2011;Nyamathi et al, 2007;Treloar et al, 2007).…”
Section: Patient Views Of Opioid Pharmacotherapy Bio-delivery Systemsmentioning
confidence: 99%
“…Berg et al, 2009;Eversman, 2010;Larance et al, 2011;Lin et al, 2010;Philbin & Zhang, 2010) and patient perspectives (e.g. Anstice et al, 2009;Conner & Rosen, 2008;Harris & McElrath, 2012;Lin et al, 2011;Nyamathi et al, 2007;Treloar et al, 2007).…”
Section: Patient Views Of Opioid Pharmacotherapy Bio-delivery Systemsmentioning
confidence: 99%
“…20 Opioid substitution therapy is also offered at community pharmacies in many countries in Europe, as well as Canada, China, India, Australia and others. [24][25][26][27][28] Sexual health services, including education on preventing transmission of bloodborne infections, are another important harm reduction strategy offered at community pharmacies. In Scotland, community pharmacists feel confident in their ability to engage IDUs and provide them with information on how to prevent acquiring or transmitting HIV, hepatitis B and hepatitis C from sexual activity.…”
Section: Key Pointsmentioning
confidence: 99%
“…They offer harm reduction services to injection drug users. In Canada, India, China, Australia, and Europe, community pharmacies are centres of opioid substitution therapy, human immune deficiency virus (HIV) and hepatitis prevention services [58][59][60][61][62][63]. A quasi-experimental study conducted in various jurisdictions in Nigeria including Abuja, Kwara, Abia and Edo states indicated that community pharmacists serve as a bridge between patients and physicians and offer varying levels of maternal and child healthcare services.…”
Section: Resultsmentioning
confidence: 99%